MAKSIMUM TEGANGAN THERMAL PADA PROSES PENCELUPAN CERAMIC STALK DI LOW PRESSURE DIE CASTING MACHINE - Hendra . (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2012)
Abstract Low pressure die casting is process to make the axi-simmetric product such as cylinder head, piston, brake drum and etc. The process is injected the molten metal with high speeds and pressure into a metallic die. The low pressure die casting process has some advantages as a low-cost and high-efficiency precision forming technique. The low pressure die casting having the permanent die and filling systems are placed over the furnace containing the molten alloy. The filling of the cavity is obtained by forcing using the pressurized gas to order a rise the molten metal into a tube, which connects the die to the furnace. The tube called stalk made from ceramics because ceramics has high temperature resistance and high corrosion resistance. However, care should be taken for the thermal stress when the tube is dipped into the molten metal. To reduce the risk of fracture it is important because fracture may happen due to the thermal stresses. In this paper, thermo-fluid analysis is performed to calculate surface heat transfer coefficient. Then, the finite element method is applied to consider the thermal stresses when the stalk is dipped into the crucible with varying the dipping speeds. It is found that the stalk with slowly dipping is better than fast dipping to reduce the thermal stress.Keywords: Thermal Stress, Stalk, Low Pressure Die Casting Machine, Finite element method